Navigating nutrition beyond elite sport: a qualitative exploration of experiences after retirement - Whillas, E. K.; Craddock, J. C.; Lambert, K. (Nutrients, 2025)
Background/Objectives: Retirement from elite sport often disrupts structured routines and performance-driven nutrition habits, leaving athletes vulnerable to maladaptive eating behaviours and body image concerns. This study aimed to explore the experiences of former elite athletes regarding healthy eating after retirement, focusing on preparedness, barriers, and enablers during the transition to post-sport life. Methods: A qualitative design was employed using semi-structured interviews with former Australian athletes (national, international, or Olympic level) recruited via snowball sampling and professional networks. Interviews were recorded, transcribed, and analysed using an inductive thematic analysis framework to identify key themes and subthemes. Results: Sixteen elite or highly trained athletes (56% female) were interviewed. Four overarching themes were apparent: (1) navigating life beyond elite sport, (2) detaching from sporting culture and belief systems, (3) reframing food, body, and control, and (4) the journey to healthy behaviours and food freedom. Participants reported identity loss, inadequate transition support, and persistent body image concerns. Over time, many described a gradual shift towards intuitive eating and improved relationships with food and self, though residual "food noise" and restrictive tendencies persisted for some. Conclusions: The findings highlight the need for athlete-centred dietetic and psychological interventions across the athletic lifecycle and post-retirement. Culture change within elite sport and the development of tailored, accessible transition resources that include digital and AI-supported tools may facilitate healthier eating behaviours and long-term wellbeing.